Former Muslims’ socio-religious discourse on social media : a speech acts analysis - Radzuwan Ab Rashid,; Almekhlafy, Sultan Saleh Ahmad; Muhammad Yasir Malik,; Hassam Ahmad Hashmi, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study aims to provide insights into the speech acts in socio-religious discourse constructed by former Malaysian Muslims on social media. This study employs a blended analytical lens consisting of Searle’s (1999) taxonomy of speech acts and van Dijk’s (1992) perspective of micro and macro speech acts. The analysis reveals that all five conventional speech act categories are represented in the discourse. But these categories do not provide insights into the real performances in the construction of discourse unless they are combined with analysis of actual performances at utterance level and at discourse level. Using blended speech act analysis, this study provides deeper insights into how and what former Muslims accomplish through their use of language while constructing anti-religious discourse on social media. The analysis revealed that from van Dijk’s (1992) perspective of speech acts, at the utterance level; argument is the most used micro-speech act followed by denial, persuasion, suggestion, rejection, warning, and assertion. At the discourse level; argument is also the most common macro-speech act followed by rejection, denial, warning, assertion, persuasion, information, and direction. This study concludes that the social media affordances enabled the former Muslims living in Islamic countries to perform speech acts and construct derogatory discourse on Islam. Further the strategic speech acts identified demonstrate former Muslims’ tendency, capacity and intention of challenging religious, especially Islamic, authoritative discourse.